2008
DOI: 10.1107/s1600536808007460
|View full text |Cite
|
Sign up to set email alerts
|

6,6,9a-Trimethyl-5,5a,6,7,8,9,9a,9b-octahydronaphtho[1,2-c]furan-1(3H)-one

Abstract: In the crystal structure of the title compound, C15H22O2, the cyclo­hexene and cyclo­hexane rings adopt half-boat and chair conformations, respectively, and the lactone ring is in an envelope conformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The chemical characterization of drimane sesquiterpenoids coincides with that obtained by X-ray studies, where a basic structural framework is shown: a trans -decalin moiety with a Δ 7(8) double bond, giving a twisted chair conformation at the second ring and conferring a planar C-7–C-8–C-12 dihedral angle of 126.7° for dendocarbin A.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…The chemical characterization of drimane sesquiterpenoids coincides with that obtained by X-ray studies, where a basic structural framework is shown: a trans -decalin moiety with a Δ 7(8) double bond, giving a twisted chair conformation at the second ring and conferring a planar C-7–C-8–C-12 dihedral angle of 126.7° for dendocarbin A.…”
Section: Resultssupporting
confidence: 71%
“…The drimane sesquiterpenoids drimenin, cinnamolide, dendocarbin A, and polygodial (Figure 1) were isolated from EtOAc extracts of the bark from the Canelo tree D. winteri. The 1 H NMR (Table S1, Supporting Information) and 13 C NMR (Table S2, Supporting Information) results are in excellent agreement with previous data. 11 ,12 The chemical characterization of drimane sesquiterpenoids coincides with that obtained by X-ray studies, 13−15 where a basic structural framework is shown: a trans-decalin moiety with a Δ 7 (8) double bond, giving a twisted chair conformation at the second ring and conferring a planar C-7−C-8−C-12 dihedral angle of 126.7°for dendocarbin A.…”
Section: ■ Results and Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…It is worth mentioning that this envelope geometry for the lactone ring is favoured by the 'outer' position of the double bond; when the location is instead 'inner' (C8 C9), the group is strictly planar, with mean deviations from planarity smaller than 0.02 Å (see, for example, Nicotra et al, 2006;Qian & Zhao, 2012;von Nussbaum et al, 2012) A search of the Cambridge Structural Database (CSD, Version 5.34; Allen, 2002) disclosed that the structure of (I) is closely related to three analogues, viz. the disteromer lactone drimenin [(II); CSD refcode DIWSEI; Brito, Ló pez- Rodríguez et al, 2008] The molecular structure of (I), with displacement ellipsoids drawn at the 30% probability level. Computer programs: CrysAlis PRO (Oxford Diffraction, 2009), SHELXS97 (Sheldrick, 2008), XP in SHELXTL (Sheldrick, 2008), SHELXL2013 (Sheldrick, 2008) and PLATON (Spek, 2009).…”
Section: Resultsmentioning
confidence: 99%